UJI EFEKTIVITAS FORMULASI SEDIAAN SALEP FRAKSI ETIL ASETAT DAUN KOPASANDA (Chromoleana odorata L.) TERHADAP PENYEMBUHAN LUKA SAYAT PADA TIKUS JANTAN WISTAR (Rattus norvegicus) - Nurasni; Elfia Neswita; Nurul A’la (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
This study aimed to test the effectiveness of an ointment made from the ethyl acetate fraction of cotton apple (Chromoleana odorata L.) leaves in accelerating the healing of cut wounds in male white mice. Empirically, cotton apple leaves have long been used as a traditional medicine to treat wounds and infections. The objectives of this study were to assess the healing time, determine the most effective concentration, and compare the effectiveness of the ethyl acetate fraction ointment with a commercially available product. This was a laboratory experimental study with a post-test only control group design. Ointment formulations were prepared in three extract concentrations: FI (5%), FII (10%), and FIII (15%), each containing 1 gram, 2 grams, and 3 grams, respectively, and included positive and negative control groups. Effectiveness testing was conducted on experimental animals, comparing all treatment groups. Observed parameters included erythema, edema, and wound closure, measured by wound length using a ruler. The results showed that the FI formulation with a 10% concentration provided the fastest healing time, with wounds healing on average on the 10th day. Statistical analysis using ANOVA test (p < 0.005) showed that the ointment preparation of ethyl acetate fraction of cottonwood leaves was effective in accelerating the healing of cuts. Tukey's further test showed a significant difference between FI with KTP, KE, K-, FII, and FIII, but there was no significant difference between FII and povidone iodine ointment.